Oxytocin and Oxytocinase in the Obese and Nonobese Parturients during Induction and Augmentation of Labor - De Tina, Annemaria; Juang, Jeremy; McElrath, Thomas F.; Baty, Jack D.; Palanisamy, Arvind (American Journal of Perinatology Reports, 2019)
Objective To investigate differences in oxytocin (OXT) biodistribution between nonobese and obese parturients during labor.Study Design Patients with body mass index (BMI) of either ≥ 18 ≤ 24.9 kg/m2 (“nonobese”) or ≥ 30 kg/m2 (“obese”) undergoing elective induction of labor were included (N = 25 each). Blood samples were collected at baseline (T0), and 20 minutes after maximal OXT augmentation or adequate uterine contractions (T1) for OXT and oxytocinase assays. A mixed-model repeated-measures analysis of variance was used to test for group versus time interaction and analysis of covariance to detect a difference in OXT level at T1. Data presented as mean ± standard deviation or median (interquartile range), with p < 0.05 considered significant.Results The mean BMIs (kg/m2) were 22.1 ± 1.6 and 35.9 ± 5.1 in the nonobese and obese groups, respectively. No differences were observed in either the duration of OXT infusion, total dose of OXT, or plasma OXT (pg/mL) either at T0 or T1. However, plasma oxytocinase (ng/mL) was significantly lower at T0 (1.41 [0.67, 3.51] vs. 0.40 [0.29, 1.12]; p = 0.03) in the obese group.Conclusion We provide preliminary evidence that the disposition of OXT may not be different between obese and nonobese women during labor.
Keywords: obesity; pregnancy; oxytocin; induction of labor; augmentation of labor; oxytocinase